Introduction to the New Testament - Thiessen, Henry Clarence, 1883-1947 (Grand Rapids, MI Eerdmans, 1943)
Includes bibliographical references and index.
Donated by John Dickson, 2002.
Keywords: BIble. N.T. -- introductions